Managing the risk of repeated violence against the intimate partner in probation service: Review of the practice in Lithuania and foreign countries - Jarutienė, Liubovė; Laurinaitytė, Ilona (Kriminologijos studijos, 2024)
According to official statistical data, each year a large number of the perpetrators of intimate partner violence (IPV) is under the supervision of Lithuanian probation service (LPS). This article analyses evidence-based measures applied for the management of the risk of repeated IPV, as well as Lithuanian and foreign practice of organising correctional work with the perpetrators of IPV. Analysis of recent practice shows that, compared to foreign countries, correctional work with this group of offenders in Lithuania often does not correspond to the principles of the Risk-Need-Responsivity model and does not address the heterogeneity of this specific group. Taking into account the good practice of foreign countries and the Lithuanian context, several suggestions are made to improve correctional work with this specific group: revising individual assessment procedures, preparing differentiated protocols for service provision, and adapting the means available at LPS for correctional work with IPV perpetrators.